Comparing the Effect of Facial Compression Bandage to That of Systemic Dexamethasone on Postsurgical Sequels after Extraction of Impacted Mandibular Third Molars: A Split-mouth Randomized Clinical Trial - Hamadi, Ibraheem; Al-Khanati, Nuraldeen Maher; Kara Beit, Zafin (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: The present study aimed to compare the clinical efficiency of facial pressure bandage, to that of intramuscular injection of dexamethasone (8 mg) on postsurgical sequels (swelling, pain, and trismus) of extraction of impacted mandibular third molar. METHODS: The study implemented a randomized split-mouth design. Patients with symmetrical bilateral impacted molars were eligible for the present trial. Sides were randomly assigned to two groups: pressure bandage group and dexamethasone group. The evaluated postsurgical sequels were extraoral swelling, trismus, and pain after 48 h and 7 days. RESULTS: The study included 42 impacted third molars (n = 42) in 21 patients with a mean age of 23.4 years. Most participants were females (66.7%). The mean postoperative swelling rates after 48 h and 7 days in pressure bandage group were found to be comparable to those of dexamethasone group. No significant difference was found in the mean rates of postoperative trismus between study groups after 48 h and 7 days. Differences in mean pain level scores between the pressure bandage group and dexamethasone group were statistically insignificant after 48 h and 7 days. CONCLUSION: The study findings showed that the effect of the pressure bandage was comparable to dexamethasone effect on the postsurgical sequels after surgical extraction of impacted mandibular third molars.